Identification of first‐stage labor arrest by electromyography in term nulliparous women after induction of labor. (19th April 2017) - Vasak, Blanka; Graatsma, Elisabeth M.; Hekman‐Drost, Elske; Eijkemans, Marinus J.; Schagen van Leeuwen, Jules H.; Visser, Gerard H.A.; Jacod, Benoit C.
Abstract: Introduction: Worldwide induction and cesarean delivery rates have increased rapidly, with consequences for subsequent pregnancies. The majority of intrapartum cesarean deliveries are performed for failure to progress, typically in nulliparous women at term. Current uterine registration techniques fail to identify inefficient contractions leading to first‐stage labor arrest. An alternative technique, uterine electromyography has been shown to identify inefficient contractions leading to first‐stage arrest of labor in nulliparous women with spontaneous onset of labor at term. The objective of this study was to determine whether this finding can be reproduced in induction of labor. Material and methods: Uterine activity was measured in 141 nulliparous women with singleton term pregnancies and a fetus in cephalic position during induced labor. Electrical activity of the myometrium during contractions was characterized by its power density spectrum. Results: No significant differences were found in contraction characteristics between women with induced labor delivering vaginally with or without oxytocin and women with arrested labor with subsequent cesarean delivery. Conclusion: Uterine electromyography shows no correlation with progression of labor in induced labor, which is in contrast to spontaneous labor.